Cross-ownership in the banking system in Vietnam - Nguyen, Minh Trang; Trinh, Minh Anh (International Journal of Scientific Research and Management (IJSRM), 2024)
The banking industry is an important component of the economy, contributing significantly to economic development and national growth. A sustainable and effective banking system will bring many benefits to the economy, minimizing disadvantages to society and the environment. The banking sector in Vietnam is currently undergoing comprehensive restructuring efforts aimed at enhancing operational efficiency and ensuring safety and sustainable development within the context of economic integration. While cross-ownership is deemed normal in economies reliant on credit, the situation in Vietnam is complicated by underdeveloped inspection and supervision activities. This raises concerns about the potential negative impacts of cross-ownership on the overall efficiency of the economy, with particular emphasis on its ramifications for the banking and financial sector. In this paper, we aim to explore the complex world of cross-ownership, taking a closer look at how it's influencing the global business scene and, more importantly, shaping the banking sector in Vietnam. Our focus is on unraveling the various aspects of cross-ownership, understanding its prevalence worldwide, and delving into the implications it holds